Pengaruh E-Money terhadap permintaan uang pada sebelum dan sesudah Covid-19 - Awan Dewanta; Andiene I’zaz Nurun Putri (Jurnal Kebijakan Ekonomi dan Keuangan, 2022)
Purpose – To examine the effect of the pandemic on changes in the number and value of e-money transactions on real money demand. Methods – Auto Regressive Distributed Lag (ARDL) time series regression. Findings – The number of e-money transactions and transaction value affect the increase in real money demand, but the number of credit card transactions reduces it in the short and long run. The pandemic effect does not increase the number of e-money transactions in the short and long term, while the pandemic effect increases the value of e-money transactions although it is temporary. Implication – Monetary authorities increase the distribution or the equalization of support facilities for e-money payment recipients, as well as the ease and security of using e-money. Originality – ARDL model analysis shows that the pandemic effect increases real money demand in both the short and long term by increasing the value of e-money transactions, while the monthly effect affects in the short term. The pandemic effect on increasing the value of e-money usage is temporary.   Abstrak Tujuan – Mengkaji efek pandemic terhadap perubahan jumlah transaksi dan nilai transaksi penggunaan e-money dalam mempengaruhi permintaan uang riil Metode – Auto Regressive Distributed Lag (ARDL) time series regression Temuan – Besaran jumlah transaksi e-money dan nilai transaksi mempengaruhi peningkatan permintaan uang riil, namun jumlah transaksi kartu kredit menurunkan permintaan uang riil dalam jangka pendek dan panjang. Efek pandemic tidak meningkatkan jumlah transaksi e-money dalam jangka pendek dan panjang, sedangkan efek pandemi meningkatkan nilai transaksi e-money meskipun bersifat sementara. Implikasi – Otoritas moneter meningkatkan penyebaran atau pemerataan fasilitas pendukung penerima pembayaran e-money, dan kemudahan dan keamanan menggunakan e-money. Orisinalitas – Dengan menggunakan analisis model ARDL, efek pandemi meningkatkan permintaan uang riil melalui peningkatan nilai transaksi e-money dalam jangka pendek dan panjang, sedangkan efek bulanan mempengaruhi permintaan uang riil jangka pendek. Efek pandemic terhadap peningkatan nilai penggunaan e-money bersifat sementara.